Material Selection Method Using Tangible and Intangible Material Properties: A Case Study of Travel Luggage - Choi, Jaeho (Metals and materials international, 2023)
Wheeled luggage has become a necessity for travel, and there is a wide range of products on the market. Many of these products are of a high quality, both functionally and aesthetically, but nevertheless, these products can suffer damage during use. For example, wheels or handles can fall off or the luggage body can be deformed or destroyed. Therefore, in this study, we evaluate selection method for appropriate materials to prevent damage to the luggage body, even under harsh usage conditions. The material selection method is a combination of two methods. One is an engineering-based material selection method using tangible material properties, and the other is a product personality-based material selection method using intangible material properties. First, the design requirements are described in terms of function, constraints, personality, and objectives. Subsequently, materials are selected from each of these perspectives. Function represents the product function, and constraints are the essential conditions that the product must have. Materials that satisfy these conditions are, thus, selected. Then, the material class is determined by the product personality, which is based on the consumers' perception of materials. Finally, the selected materials are ranked using the objectives, and the final material is selected by comparing the supporting information between the materials in the upper ranking. Graphical Abstract